Reformasi Manhaj al-Mufassirin dalam Tafsir al-Manar karya Muhammad Abduh dan Rasyid Rida: The Reform of Manhaj al-Mufassirin in the Tafsir al-Manar of Muhammad Abduh and Rashid Rida: A Methodological Shift - Herlina Yunita Amroin; Syamsu Syauqani (Program Studi Ilmu Al-Quran dan Tafsir STIU Darul Quran, 2026)
Reform within the Islamic scholarly tradition refers to efforts to renew thought and methodology so that they remain relevant to changing times without abandoning the religion's fundamental principles. This study aims to analyze the form of methodological reform in manhaj al-mufassirin presented in Tafsir al-Manar by Muhammad Abduh and Rashid Rida, particularly regarding the integration of rationality, maqasid al-syariah, and the orientation toward social reform in Quranic interpretation. This research employs a qualitative approach, using content analysis of the Tafsir al-Manar text, complemented by a contextual examination of the reformist thought of both scholars in their responses to the social, political, and intellectual challenges of the early modern period. The findings indicate that the methodological reform introduced by al-Manar is grounded in efforts to restore the Quran's role as a guide for societal transformation through rational, progressive, and public-oriented interpretation. The rationality employed is not speculative but seeks to harmonize revelation with the advancement of scientific knowledge. Meanwhile, maqasid al-syariah serves as a normative framework for interpreting social, legal, and ethical verses. These findings demonstrate that al-Manar advances a modern exegetical methodology that not only promotes methodological reform but also contributes significantly to the reconstruction of contemporary Islamic civilization.